Distinct patterns of progressive gray and white matter degeneration in amyotrophic lateral sclerosis. Issue 5 (15th December 2021) - Ishaque, Abdullah; Ta, Daniel; Khan, Muhammad; Zinman, Lorne; Korngut, Lawrence; Genge, Angela; Dionne, Annie; Briemberg, Hannah; Luk, Collin; Yang, Yee‐Hong; Beaulieu, Christian; Emery, Derek; et al.
Abstract: Progressive cerebral degeneration in amyotrophic lateral sclerosis (ALS) remains poorly understood. Here, three‐dimensional (3D) texture analysis was used to study longitudinal gray and white matter cerebral degeneration in ALS from routine T1‐weighted magnetic resonance imaging (MRI). Participants were included from the Canadian ALS Neuroimaging Consortium (CALSNIC) who underwent up to three clinical assessments and MRI at four‐month intervals, up to 8 months after baseline ( T 0 ). Three‐dimensional maps of the texture feature autocorrelation were computed from T1‐weighted images. One hundred and nineteen controls and 137 ALS patients were included, with 81 controls and 84 ALS patients returning for at least one follow‐up. At baseline, texture changes in ALS patients were detected in the motor cortex, corticospinal tract, insular cortex, and bilateral frontal and temporal white matter compared to controls. Longitudinal comparison of texture maps between T 0 and T max (last follow‐up visit) within ALS patients showed progressive texture alterations in the temporal white matter, insula, and internal capsule. Additionally, when compared to controls, ALS patients had greater texture changes in the frontal and temporal structures at T max than at T 0 . In subgroup analysis, slow progressing ALS patients had greater progressive texture change in the internal capsule than the fast progressing patients. Contrastingly, fast progressing patients had greater progressive texture changes in the precentral gyrus. These findings suggest that the characteristic longitudinal gray matter pathology in ALS is the progressive involvement of frontotemporal regions rather than a worsening pathology within the motor cortex, and that phenotypic variability is associated with distinct progressive spatial pathology. Abstract : In this study, we use MRI texture analysis to detect progressive cerebral degeneration in amyotrophic lateral sclerosis (ALS). Here, we demonstrate distinct spatiotemporal patterns of degeneration related to clinical phenotypes in patients with ALS.